Multiple switching tables direct power control of active front‐end rectifiers. Issue 6 (1st June 2014) - Norniella, Joaquín G.; Cano, José M.; Orcajo, Gonzalo A.; Rojas, Carlos H.; Pedrayes, Joaquín F.; Cabanas, Manés F.; G. Melero, Manuel
Abstract : Direct power control (DPC) is one of the best well‐known methods used in three‐phase active rectifiers interfacing regenerative loads to the ac grid. The DPC strategy is based on a straightforward regulation of instantaneous real and reactive powers. A switching table (ST) is used to track the real and reactive power references by selecting an appropriate switching state as a function of the estimated position of the grid voltage space vector in the α–β plane. Certain advantages are observed if different STs are used during the rectifier and inverter (regenerative operation) modes or according to the sequence of the ac grid. Furthermore, the STs can be designed to achieve a fast transient behaviour or to improve the efficiency of the converter by minimising the switching losses. Thus, the use of a single table, as stated in traditional proposals, is far from the optimal solution when the full duty cycle of the device is considered. This study introduces the multiple STs DPC as a simple unified control strategy intended to attain the best performance of the DPC method at any operation point. This strategy is demonstrated by means of simulation and experimental tests.